(untitled) (Nigerian Journal of Technology, 2002)
“Egusi” is the common Nigerian name for the food seeds considered to be of the Citrullus Sp. and inclusively known as “melon” seeds. On the basis of experience gained in the design and construction of a spinning disc “melon” seed shelling machine for large scale factory applications, a kitchen appliance of shelling egusi was designed. The prototype was constructed as an accessory to a kitchen blender. The performance test showed that the appliance performed satisfactorily with a shelling effectiveness of nearly 100% and minimum percentage breakage of about 8% at a capacity of about 10 kg/h.